Performance of groundnut (Arachis hypogaea) cultivars for higher productivity in hilly ecosystem - ANSARI, M A; CHOUDHURY, B U; ROY, S S; SHARMA, S K; SINGH, I M; SINGH, A L; PRAKASH, N (The Indian Journal of Agricultural Sciences, 2020)
Low productive cereals (rice and maize/mixed cropping) in the Jhum degraded abiotic stressed soils (from acidity and moisture deficit) of rainfed hilly ecosystem of Northeast India (NEI) restrict jhumias socio-economic upliftment. Shift in cropping pattern to stress-tolerant groundnut cultivars may provide an option in such a situation. We evaluated the performance of 26 improved cultivars of groundnut for four consecutive years (2013-2016) in terms of suitable agronomic and physiological traits for higher productivity in such soils under rainfed hilly ecosystem of NEI (Manipur) and compared their performances with one popular local check (JL-24). Few improved cultivars (GG-21, TG 37-A, GG-11, TKG-19-A, ICGV-86590 and ICGS-76) yielded significantly (P<0.05) higher (2.72 to 3.35 t/ha) than the local check (2.09 t/ha), primarily because of their better agronomic (leaf area and root dry weight) and physiological (nodulation, chlorophyll and proline contents) traits. Higher agronomical and physiological attributes also led higher production of biomass (above and below ground) than other cultivars. More carbon addition from higher biomass of these cultivars will help in restoration of soil health while higher pod productivity will improve socio-economy of the jhumias. These few selected, sensitive agronomic and physiological traits, thus, can be explored for selection of suitable groundnut cultivars, highly productive yet adaptive and restorative to Jhum degraded acid soils in the rainfed hilly ecosystem of NEI as well as in other such similar agro-ecological regions.